Defending against heap overflow by using randomization in nested virtual clusters - TEY, Chee Meng (Institutional Knowledge at Singapore Management University, 2013)
Heap based buffer overflows are a dangerous class of vulnerability. One countermeasure is randomizing the location of heap memory blocks. Existing techniques segregate the address space into clusters, each of which is used exclusively for one block size. This approach requires a large amount of address space reservation, and results in lower location randomization for larger blocks.